Bias in Radiology Resident Selection: Do We Discriminate Against the Obese and Unattractive?. (November 2019) - Maxfield, Charles M.; Thorpe, Matthew P.; Desser, Terry S.; Heitkamp, Darel E.; Hull, Nathan C.; Johnson, Karen S.; Koontz, Nicholas A.; Mlady, Gary W.; Welch, Timothy J.; Grimm, Lars J.
Abstract : Purpose: To evaluate for appearance-based discrimination in the selection of radiology residents. Method: A deception study simulating the resident selection process examined the impact of attractiveness and obesity on resident selection. Seventy-four core faculty from 5 academic radiology departments reviewed mock residency applications in September and October 2017. Each application included demographic information and a photograph, representing a prespecified distribution of facial attractiveness and obesity, combined with randomized academic and supporting variables. Reviewers independently scored applications for interview desirability. Reviewer scores and application variables were compared using linear mixed fixed- and random-effects models. Results: Reviewers evaluated 5, 447 applications (mean: 74 applications per reviewer). United States Medical Licensing Examination Step 1 scores were the strongest predictor of reviewer rating (B = 0.35 [standard error (SE) = 0.029]). Applicant facial attractiveness strongly predicted rating (attractive vs unattractive, B = 0.30 [SE = 0.056]; neutral vs unattractive, B = 0.13 [SE = 0.028]). Less influential but still significant predictors included race/ethnicity (B = 0.25 [SE = 0.059]), preclinical class rank (B = 0.25 [SE = 0.040]), clinical clerkship grades (B = 0.23 [SE = 0.034]), Alpha Omega Alpha membership (B = 0.21 [SE = 0.032]), and obesity (vs not obese) (B = −0.14 [SE = 0.024]). Conclusions: Findings provide preliminary evidence of discrimination against facially unattractive and obese applicants in radiology resident selection. Obesity and attractiveness were as influential in applicant selection for interview as traditional medical school performance metrics. Selection committees should invoke strategies to detect and manage appearance-based bias.